A Prospective Study to Assess the Best Optimal Dose of Tacrolimus before Renal Transplantation and Its Impact on Graft Survival and Patient Outcome in Renal Transplant Recipients - Niranjan Gogoi; Charu Jain; Megha Agarwal; Dhananjay Agarwal; Ajay Gupta; Munesh Kumar (Indian Journal of Transplantation)
Background: The treatment of renal transplantation has been revolutionized by the advent of calcineurin inhibitors like tacrolimus (TAC). There is a wide variation in the expression of cytochrome p450 enzyme for TAC metabolization in Indian population. This variation may lead to unpredictable outcome in renal transplants (RTs). Early identification of patients at risk may help to improve graft outcome. Aims and Objectives: To assess the best optimal dose of tacrolimus and its impact on graft survival and patient outcome in renal transplant recipients. Materials and Methods: A prospective longitudinal study was conducted in the Department of Nephrology for 1 year after due approval. Patients with end-stage renal disease undergoing RT on TAC with available TAC trough concentration 1 month before transplantation were included and analyzed for graft function and patient outcome in terms of adequate immunosuppression and renal function. Results: Among total 30 recipients, 17 (56.7%) were fast-TAC metabolizers (concentration-to-dose [C/D] ratio <1 μg/ml·1/mg) and the rest 13 (43.3%) were slow-TAC metabolizers (C/D ratio ≥1 μg/ml·1/mg). TAC dose modification was done in 14 (86%) fast metabolizers and 6 (46.15%) slow metabolizers (adapted group) 3 days before RT to keep the drug in therapeutic range. Among the adapted group, 15/20 patients (fast metabolizers – 10 and slow metabolizers – 5) had achieved early target trough levels (at day 4) in comparison to the control group 3/10 (fast metabolizers – 0 and slow metabolizers – 3) (P < 0.05). Three cases of biopsy-proven acute graft rejection were found among fast-TAC metabolizers, contrary to one case among slow-TAC metabolizers (P = 0.182). One patient showed TAC-related toxicity in biopsy. Conclusion: Optimizing the dose of TAC before renal transplantation may facilitate individualization of immunosuppression and can improve graft outcome.